2016
DOI: 10.1017/dmp.2016.88
|View full text |Cite
|
Sign up to set email alerts
|

Education in Disaster Management: What Do We Offer and What Do We Need? Proposing a New Global Program

Abstract: This program enables interagency cooperation and collaboration and could be used to increase and improve decision-makers' understanding of disaster managers' capabilities; at the strategic/tactical level to promote the knowledge and capability of the disaster managers themselves; and as continuing education or further career development for disaster managers at the operational level. (Disaster Med Public Health Preparedness. 2016;10:854-873).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 18 publications
2
43
0
Order By: Relevance
“…A lot of effort has gone into creating effective triage teaching and training methods [65,72,148,149]. Courses such as ATLS and PHTLS have had an impact on trauma care education, and take place worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of effort has gone into creating effective triage teaching and training methods [65,72,148,149]. Courses such as ATLS and PHTLS have had an impact on trauma care education, and take place worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Learning is multidimensional and therefore requires multiple measures of different types of outcomes [73]. A good assessment method should be simple and flexible, but also based on theory [72]. One method of evaluation often used in triage training is to test learners before and after an intervention [84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a Swedish perspective, such an education can be given in various stages, offering different levels of knowledge, skills, and competency based on the individual's willingness, background, and interest. Similar programs have already been suggested [56]. Evaluation of the content and length of one of the "stop the bleed" courses, in San Antonio, Texas, USA in 2017 showed that just a short course, 1 h, is enough for civilians to both feel comfortable in stopping bleedings using tourniquets and performing it correctly, by applying pressure [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency service, medical plant, and ambulance service point location and layout problem are surveyed by many authors [17][18][19][20][21][22][23][24]. While some surveys cover only location layout, the other relatives from these research area such as disaster [25][26][27]. Some studies are impressed by the medical failure of patients in a disaster such as acute renal failure [28].…”
mentioning
confidence: 99%